Agrotropolis : youth, street, and nation in the new urban Guatemala - Way, John T. (John Thomas), 1966- (University of California Press, 2021)
"In this comprehensive book, historian J.T. Way examines and traces the developments of Guatemalan urbanization and youth culture since 1983. In case studies that bring together political economy, popular music, and everyday life, Way explores the rise of urban space in towns seen as quintessentially "rural" and showcases grassroots cultural assertiveness. In a post-revolutionary era, youth coming of age on the globally inflected city street have used popular culture as one means of creating a new national imaginary that rejects Guatemala's racially coded system of castes. Drawing on local sources, deep ethnographies, and the digital archive, Agrotropolis places working-class Maya and mestizo hometowns and creativity at the center of planetary urban history"--